PENGARUH SUSTAINABLE BRAND EXPERIENCE DAN PERCEIVED VALUE TERHADAP BRAND LOYALTY DI MODERASI CONSIOUS CONSUMPTION DALAM PERSPEKTIF BISNIS ISLAM (PADA KONSUMEN THE BODY SHOP DI BANDAR LAMPUNG) - Olivia Regita Putri; Fatih Fuadi; Sherly Etika Sari (JURNAL LENTERA BISNIS, 2026)
The development of the beauty and personal care industry has encouraged companies to implement sustainability concepts as a strategy to enhance consumer loyalty. The Body Shop is one of the companies that promotes the concept of ethical beauty through environmentally friendly products and sustainability-oriented social campaigns. However, increasing consumer awareness of environmental issues does not always directly lead to brand loyalty due to the phenomenon of the attitude–behavior gap.  This study aims to analyze the influence of Sustainable Brand Experience and Perceived Value on Brand Loyalty with Conscious Consumption as a moderating variable among The Body Shop consumers in Bandar Lampung. This research employed a quantitative approach using a survey method through questionnaire distribution to The Body Shop consumers in Bandar Lampung. The sampling technique used was purposive sampling with a total of 100 respondents. The data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results indicate that Sustainable Brand Experience does not have a significant effect on Brand Loyalty. Meanwhile, Perceived Value has a positive and significant effect on Brand Loyalty. The moderating variable, Conscious Consumption, was unable to moderate the relationship between Sustainable Brand Experience and Perceived Value on Brand Loyalty. However, Conscious Consumption has a direct positive and significant effect on Brand Loyalty. These findings suggest that consumer loyalty is more strongly influenced by perceived value and consumption awareness than by sustainable brand experience directly. From the perspective of Islamic business, these findings are consistent with Islamic consumption principles that emphasize halal, good, conscious, and non-excessive consumption. This study is expected to provide both theoretical and practical contributions for companies in developing sustainable marketing strategies based on value and consumer awareness.